Nickel distribution and isotopic fractionation in a Brazilian lateritic regolith: Coupling Ni isotopes and Ni K-edge XANES. (1st June 2018) - Ratié, G.; Garnier, J.; Calmels, D.; Vantelon, D.; Guimarães, E.; Monvoisin, G.; Nouet, J.; Ponzevera, E.; Quantin, C.
Abstract: Ultramafic (UM) rocks are known to be nickel (Ni) rich and to weather quickly, which makes them a good candidate to look at the Ni isotope systematics during weathering processes at the Earth's surface. The present study aims at identifying the Ni solid speciation and discussing the weathering processes that produce Ni isotope fractionation in two deep laterite profiles under tropical conditions (Barro Alto, Goiás State, Brazil). While phyllosilicates and to a lower extent goethite are the main Ni-bearing phases in the saprolitic part of the profile, iron (Fe) oxides dominate the Ni budget in the lateritic unit. Nickel isotopic composition (δ 60 Ni values) has been measured in each unit of the regolith, i.e., rock, saprock, saprolite and laterite (n = 52). δ 60 Ni varies widely within the two laterite profiles, from −0.10 ± 0.05‰ to 1.43 ± 0.05‰, showing that significant Ni isotope fractionation occurs during the weathering of UM rocks. Overall, our results show that during weathering, the solid phase is depleted in heavy Ni isotopes due to the preferential sorption and incorporation of light Ni isotopes into Fe oxides; the same mechanisms likely apply to the incorporation of Ni into phyllosilicates (type 2:1). However, an isotopically heavy Ni pool is observed in the solid phase at the bottom of the saprolitic unit. This feature can be explained by two hypotheses that are not mutually exclusive: (i) a depletion in light Ni isotopes during the first stage of weathering due to the preferential dissolution of light Ni-containing minerals, and (ii) the sorption or incorporation of isotopically heavy Ni carried by percolating waters (groundwater samples have δ 60 Ni of 2.20 and 2.27‰), that were enriched in heavy Ni isotopes due to successive weathering processes in the overlying soil and laterite units.